2017
DOI: 10.2147/tcrm.s138355
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of respiratory symptoms for the diagnosis of pollen-induced seasonal asthma among children and adults in Inner Mongolia

Abstract: BackgroundThe diagnosis of asthma is made on the basis of variable respiratory symptoms and supported by objective evidence of variable airflow limitation. However, spirometry and bronchoprovocation tests may not be routinely available in resource-scarce settings or in the context of large-scale epidemiological studies. There is a gap in knowledge about the predictive value of respiratory symptoms for the diagnosis of pollen-induced asthma.ObjectiveThe aim of this study was to investigate the predictive value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Only three other studies assessed the accuracy of symptoms to diagnose asthma in school-aged children consecutively referred to paediatric hospitals [20][21][22]. They all found that reported wheeze was sensitive (ranging 0.75-0.86) but not specific (0.64-0.73) and that frequent wheeze and awakening due to dyspnoea were specific (0.84-0.90) but not sensitive (0.33-0.54), which is in line with our findings.…”
Section: Fev1/fvc and Bronchodilator Reversibility Had A Low Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Only three other studies assessed the accuracy of symptoms to diagnose asthma in school-aged children consecutively referred to paediatric hospitals [20][21][22]. They all found that reported wheeze was sensitive (ranging 0.75-0.86) but not specific (0.64-0.73) and that frequent wheeze and awakening due to dyspnoea were specific (0.84-0.90) but not sensitive (0.33-0.54), which is in line with our findings.…”
Section: Fev1/fvc and Bronchodilator Reversibility Had A Low Accuracymentioning
confidence: 99%
“…Symptom definitions differed between studies, especially those for cough, which results in a wide range of sensitivities and specificities that cannot be compared [20][21][22]. Five other studies assessed the accuracy of diagnostic tests in school aged children.…”
Section: Fev1/fvc and Bronchodilator Reversibility Had A Low Accuracymentioning
confidence: 99%
“…6 A bacterial or viral infection can cause pathological Cough, the presence of an irritant or allergen, or both. 7 Acute Respiratory infections can affect the upper or lower respiratory tract, and the cough results might be productive or non-productive for sputum. A cough that does not produce phlegm is typically called a "dry" cough.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of the disease in pediatric patients is usually based on clinical symptoms and precise anamnesis. Pulmonary function tests which are commonly used in adults has an age-limit for children and usually are not used for toddlers [3,4].…”
Section: Introductionmentioning
confidence: 99%